DNA repair enzymes of the Antarctic Dry Valley metagenome - Rzoska-Smith, Elizabeth; Stelzer, Ronja; Monterio, Maria; Cary, Stephen C.; Williamson, Adele (Frontiers in Microbiology, 2023)
Microbiota inhabiting the Dry Valleys of Antarctica are subjected to multiple DNA-damaging stressors such as desiccation, high UV fluxes and multiple freeze-thaw cycles. To identify novel or highly-divergent DNA-processing enzymes that may enable effective DNA repair, we have sequenced metagenomes from 30 sample-sites which are part of the most extensive Antarctic biodiversity survey undertaken to date. We then used these to construct wide-ranging sequence similarity networks from protein-coding sequences and identified candidate genes involved in specialized repair processes including unique nucleases as well as a diverse range of ATP-dependent DNA ligases implicated in stationary-phase DNA repair processes. In one of the first direct investigations of enzyme function from these unique samples, we have heterologously expressed and assayed a number of these enzymes, providing insight into the mechanisms that may enable resident microbes to survive these threats to their genomic integrity.